The bizarre ‘metatherians’ Groeberia and Patagonia, late surviving members of gondwanatherian mammals - Chimento, Nicolás Roberto (2015)
Cenozoic mammalian faunas from South America contrast with those of the other continents by the great diversification of metatherian mammals. Among the later, a wide range of morphological disparity have been reported, and several bizarre mammals have been assigned to such clade, based mainly on biogeographical grounds. Outstanding examples of bizarre mammals referred to as Metatheria are the Eocene Groeberia and the Miocene Patagonia. Recent discoveries indicate that South America possessed a more diverse faunal composition than previously thought, and it became evident that many Mesozoic holdovers (e.g. australosphenidans, gondwanatherians and dryolestoids) surpassed the K/T boundary, thus forming part of the Cenozoic faunas. The Cenozoic taxa Patagonia and Groeberia exhibit several similarities with the Gonwanatheria, including rodent-like jaws with enlarged incisives, molariform cheek-teeth, anteriorly extended masseteric fossa and palinal mastication among other features. The inclusion of Gondwanatheria, Patagonia and Groeberia within an abarcative phylogenetic analysis resulted in close phylogenetic relationships among these taxa. Such hypothesis indicates that Cretaceous relics in the Cenozoic of South America were more diversified than previously thought.